NUMERICAL PERFORMANCE ANALYSIS OF DELTA VORTEX GENERATOR LOCATED UPSTREAM OF IN-LINE TUBE BUNDLE - Ozsen, Mete; Yildiz, Sebiha (VINCA INST NUCLEAR SCI, 2024)
The effect of the delta vortex generator located upstream of the in-line tube bundle on the heat transfer and pressure loss for cross-flow air was numerically investigated. The best accurate results were obtained by using the Realizable k-epsilon model with the standard wall function. In order to increase the accuracy of the numerical model, production limit and curvature correction coefficients that depend on the inlet air velocity were used. The average error in heat transfer and pressure loss in the range of Re = 3000 and 13000 was obtained as 4.4% and 9.4%, respectively. The distance between the tube bundle and vortex generator, angle of attack, and pitch were analyzed parametrically. In all vortex generator designs, upward secondary flows in front of tubes were observed between the rows. A maximum 16.6% improvement in the average Nusselt number and a maximum 42% penalty in pressure loss were obtained. The angle of attack is the parameter that affects the heat transfer the most. When the changes in both heat transfer and pressure loss are taken into account, for Re > 9500, performance is positively affected with almost every vortex generator design.
Keywords: delta winglet; vortex generator; in-line tube bundle; numerical analysis; heat transfer enhancement; HEAT-TRANSFER CHARACTERISTICS; COMMON-FLOW; PLATE-FIN; OPTIMIZATION; ENHANCEMENT; BANK; EXCHANGER; Thermodynamics